Kontraversi Foreign Direct Investment dan Solusinya Bagi Negara - Silsila Asri (Department of International Relations, Universitas Andalas, 2015)
Foreign Direct Investment (FDI) is one of the essential capital sources for developingcountries which provide large contribution in economic development trough transfer of asset, good corporate governance and especially technology. This expectation is not always provide positive impact to the recipient countries. FDI, which is often implemented in Multi National Corporation, also becomes a tool for the developed countries to control the economic activities in developing countries in pursuing their benefit and interest. Sometimes, those MNCs also have a signifincance influence in political activities of recipient countries. Beside that, MNCs not always provide large attention to the community development. From this condition, debate about the role of state in managing of FDI emerged in political economic discourses. This paper describes about one of alternative thought how state copes with globalization. FDI is one of phenomena which emerged as the concequnces of globalization.Ian Clark suggested two perceptions about the relation of state and globalization. First, globalization has significance implication in eroding the state capacity as economic actor in international stage. Second, state is the key element in globalization process, in this perception there is a position shift of the state from state retreat to state adaptation. This paper conclude that, state also has capacity to control FDI dan globalization which accompanied it’s flow. State must place itself as business actor which has competitiveness. Keywords: Foreign Direct Investment,Globalization, State retreat, state adaptation